PERBANDINGAN SISTEM HUKUM INDONESIA DENGAN HONGARIA TENTANG PERLINDUNGAN HAK PEKERJA PEREMPUAN - Sa’diyah, Ratu Halimatus; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This paper compares protection for female workers in Hungary and Indonesia. The civil law systems in both countries are the same, but there are differences in the employment laws that apply to female employees. Using primary and secondary data, a normative approach and qualitative methodology were used to conduct this research. This article serves as a data source that can provide insight into the differences in legal arrangements regarding working women between the two countries in which the research was conducted. The findings of this research make it clear that although there are certain similarities and variations between the Hungarian and Indonesian legal frameworks for female workers, Hungary's labor law codification system is superior to Indonesia's legal codification system.Keywords: Comparison of Legal Systems, Women Workers, Legal Codification.